El fogón de Lina: Juego de mesa sobre alimentación para adultos mayores diabéticos (2024)
This project originates from the need to provide a complementary tool that facilitates access to and assimilation of information about diabetes in a more didactic way for the elderly in Colombia. This group faces difficulties in understanding and accessing key information about their diet due to the lack of specific resources (E. Montañez, personal communication, October 31, 2023). Through positive design (Jiménez, Pohlmeyer, & Desment, 2016b) and design thinking (Universitat Oberta de Catalunya, n.d.), a board game is proposed that simulates the action of cooking healthily, allowing the elderly to interact playfully with nutritional information.